A cDNA encoding tyrosinase-related protein maps to the brown locus in mouse. - Jackson, I J (1988)
A mouse melanoma cDNA clone was isolated by virtue of its reactivity with two antisera raised against tyrosinase (EC 1.14.18.1) from two species, hamster and mouse. The cDNA (5A) cross-hybridizes with another, pMT4 [Shibahara, S., Tomita, V., Sakakura, T., Nager, C., Bhabatosh, C. & Muller, R. (1986) Nucleic Acids Res. 14, 2413-2427], previously thought to encode mouse tyrosinase. Two other cDNAs, one human and one mouse, have been reported recently [Kwon, B. S., Haq, A. K., Pomerantz, S. H. & Halaban, R. (1987) Proc. Natl. Acad. Sci. USA 84, 7473-7477; and Yamamoto, H., Takeuchi, S., Kudo, T., Makino, K., Nakata, A., Shinoda, T. & Takeuchi, T. (1987) Jpn. J. Genet. 62, 271-277] as candidates for tyrosinase, and they map at or very close to the mouse albino (c) locus. The proteins they encode are very similar to each other but are distinct from (although related to) the pMT4-encoded protein. Here I use recombinant inbred strains to localize pMT4 at or close to the mouse brown (b) locus. I suggest that the gene mapping to c is the authentic tyrosinase gene, whereas that mapping to b encodes a tyrosinase-related protein. All b mutations in laboratory strains are associated with the same diagnostic Taq I fragment, suggesting that all derive from the same original mutation. I discuss possible function(s) of the tyrosinase-related protein.